PERANCANGAN BANGKU PENDEK (DINGKLIK) BERBAHAN PLASTIK DENGAN BANTUAN SIMULASI CAD/CAE - Joko Waluyo (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2021)
Injection Molding is a thermoplastic material processing method in which the material that melts due to heating is injected by a plunger into the mold and then cooled until the material is solid, and removed from the mold. The purpose of this design is to determine the maximum load that can be accepted by the short bench (Dingklik), and to design the dimensions of the bench, while the design stages are as follows: starting from the design of the bench using CAD/CAE software, and machining simulation using can CAM software. Data input simulation is performed using the CAM software engine. The maximum weight of the respondent is 95 kg, and the load chosen to be safe in this design is 190 Kg (1862,9 N) The results of the design of the bench obtained the following data: length 350 mm, width 250 mm and height 180 mm, the material used is Polypropylene, the surface area of the object is 409923 mm2, the total volume with the gatting system is 776493,9461 mm3, and the maximum load that the material can withsatand is 2551.3995 Newtons.